PEROGRAM PENINGKATAN SEMANGAT BELAJAR KEPADA ANAK-ANAK MDA DI KAMPUNG TEGAL HEAS PURWAKARTA - Aulia, Gina; Setiawan, Usep (Penerbit Widina, Widina Media Utama, 2023)
This research aims to increase the enthusiasm for learning for MDA children in Kampung Tegal Heas Purwakarta. With the MDA children in Tegal Heas, they are very enthusiastic about participating in learning at MDA. In Tegal Heas the community is very minimal, in fact the children in Tegal Heas are only approximately 15 children, these children are from grades 1, 2, 3, 5 and 6. At least the children in Tegal Heas they don't never gave up on studying religion and general science, they went to school to go down from the mountain to a neighboring village, even the access roads were very far away and children going for walks were not allowed to use motorbikes because that was a regulation from the school so there was no feeling of social jealousy. Madrasah Diniyah Takmiliyah (MDA) is an Islamic educational institution that has been known since the early development of Islam in the archipelago. At that time, Islamic teachings developed naturally through a process of acculturation that proceeded slowly and peacefully and eventually became an integral part of people's lives.ABSTRAKPenelitian ini bertujuan untuk program peningkatan semangat belajar terhadap anak-anak MDA di Kampung Tegal Heas Purwakarta, Dengan adanya MDA anak-anak di Tegal Heas, mereka sangat antusias dalam mengikuti pembelajaran di MDA. Di Tegal Heas tersebut masyarakanya sangat minim, bahkan anak-anak yang ada di Tegal Heas kurang lebih hanya 15 orang anak, anak-anak tersebut dari kelas 1, 2, 3, 5, dan 6. Sedikitnya anak-anak di Tegal Heas mereka tidak pernah menyerah dalam belajar ilmu agama maupun ilmu umum, mereka sekolah harus turun dari gunung ke perkampungan tetangga, bahkan akses jalan yang sangat jauh dan anak-anak berangkat jalan kaki tidak boleh ada yang menggunakan sepedah motor karena itu sudah peraturan dari sekolahnya agar tidak ada rasa cemburu sosial. Madrasah Diniyah Takmiliyah (MDA) merupakan lembaga pendidikan Islam yang sudahdikenal sejak awal perkembangan Islam di Nusantara. Pengajaran Islam saat itu berkembang alamiah melalui proses alkuturasi yang berjalan secara perlahan dan damai dan akhirnya menjadi bagian tak terpisahkan dari kehidupan masyarakat.